Clinical Profile of Posterior Circulation Stroke: A Prospective Study at Dhaka Medical College Hospital (Bangladesh Medical Journal, 2022)
Studies regarding clinical characteristics of stroke involving the posterior circulation territory of the brain in Bangladesh are rare although large number of patients were found in hospital admission and with a high morbidity and mortality. Study for better understanding of the clinical features, risk factors and aetiologies of posterior circulation stroke (PCS) may be very helpful for early diagnosis, treatment, and also for setting primary and secondary prevention strategies. The objective of the study was to identify clinical features and short-term outcome of PCS. Adult patients admitted in Dhaka Medical College Hospital with clinical features consistent with posterior circulation stroke involving brain stem or, cerebellum or thalamus or occipital area and confirmed by computer tomography (CT) scan of brain were the the cases as respondents. Few cases were needed MRI of brain to confirm diagnosis. This was a hospital based prospective observational study with descriptive and analytical component. Sample was selected from the study population by purposive type of non-probability sampling technique. Sample size was 30. A semi-structured questionnaire was prepared containing patients’ profile as well as stroke patients’ reporting form which included all the essential information regarding clinical profile of PCS as well as short term outcome. Analysis was done using Statistical Package for the Social Sciences (SPSS) software. Thirty consecutive cases of strokes involving posterior circulation territory were included in the study according to inclusion and exclusion criteria.  Male female ratio was 1.7:1. Most of the patients in both sexes were affected after the age of 50 years. Hemorrhagic PCS was significantly higher than ischaemic PCS. Among hemorrhagic PCS common symptoms were decreased level of consciousness and motor disturbances. Most common clinical sign in ischemic PCS is impaired consciousness which was present in 55.6% of the total ischemic PCS cases. Whereas this sign was present in all the cases of hemorrhagic PCS (100%). Like presenting symptoms, most of the clinical signs were also more common in hemorrhagic PCS. But few clinical signs were more common in ischemic strokes, such as cranial nerve involvement and nystagmus. Commonest predisposing factors were tobacco abuse, hypertension and dyslipidemia. Mortality was higher in hemorrhagic PCS than ischemic PCS within 7 days of follow up.Bangladesh Med J. 2021 Sept; 50(3): 20-25